2020
DOI: 10.3389/fpsyg.2019.02987
|View full text |Cite
|
Sign up to set email alerts
|

Transition From Crawling to Walking Changes Gaze Communication Space in Everyday Infant-Parent Interaction

Abstract: Acquisition of walking changes not only infants' locomotion itself but also infants' exploratory behavior and social interaction, such as gaze communication. To understand the ecological context in which gaze communication occurs and how it changes with walking development from the point of view of the spatial arrangement of infants, parents, and objects, we analyzed longitudinal data of daily eye contact scenes recorded from head-mounted eye trackers worn by parents as infants grew from 10 to 15.5 months, foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…Infants may selectively attend to objects to engage in object manipulation and explore object properties [15,[17][18][19][20]. Second, body posture (e.g., prone, sitting, and upright) shapes infants' visual attention [21][22][23][24]. Whereas in a screen-viewing study participants are seated with information easily viewed in front of the face, real-world visual attention is shaped by the orientation of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Infants may selectively attend to objects to engage in object manipulation and explore object properties [15,[17][18][19][20]. Second, body posture (e.g., prone, sitting, and upright) shapes infants' visual attention [21][22][23][24]. Whereas in a screen-viewing study participants are seated with information easily viewed in front of the face, real-world visual attention is shaped by the orientation of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Fecha de aceptación: 31-05-21 Víctor Miguel Ángel Burbano Pantoja victor.burbano@uptc.edu.co der por una mejora en su calidad vital e incluso en su autoestima infantil (Lizarazo, Burbano & Valdivieso, 2020). En general, un aspecto central de la motricidad lo constituye la CM, la cual puede promoverse desde el hogar (Yamamoto, Sato & Itakura, 2020) o en la escuela (Reyes, et al, 2019). La CM ha sido estudiada en diversos contextos, en condiciones normales (Grohs, Reynolds, Dewey & Lebel, 2018;Oberer, Gashaj & Roebers, 2018) o en individuos con alguna discapacidad (Vargas, Acaro, Pintado & Jurado, 2021;Keawutan, Bell, Oftedal, Davies, Ware, & Boyd et al, 2018;VanCappellen, VanAbswoude, Krajenbrink & Steenbergen, 2018).…”
Section: Influencia De Un Programa De Juegos Pueriles Sobre La Coordinación Motriz En Estudiantes De Educación Básica Influence Of a Chilunclassified
“…Prior work indicates that walking infants gesture, vocalize, and look to their caregivers more often than crawlers do (Clearfield, 2011; Clearfield et al, 2008; Walle, 2016; Yamamoto et al, 2020). For example, Clearfield (2011) reported that socially directed vocalizations and gestures doubled when infants were walking, compared to a prior session in which infants crawled or moved in a baby‐walker.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature suggests that walking has a cascading effect on infant communication, influencing how often infants gesture, vocalize, and approach caregivers, and in turn, caregiver responses (e.g., Clearfield, 2011; Clearfield et al, 2008; Karasik et al, 2014; Walle, 2016; Yamamoto et al, 2020). However, there are important limitations to this work.…”
Section: Introductionmentioning
confidence: 99%